TASTE BLINDNESS AMONG MEDICAL STUDENTS - Khokhar, Abdul Rehman; Iqbal, Tehseen; Yousafi, Naveed Atif; Latif, Malik Shah Zaman (Pakistan Journal of Physiology, 2018)
Introduction: Modern research has reported variations in taste that results in food and beverage consumption. This is true that 15–25% of population is born with taste blindness to phenylthiocarbamide (PTC). This study aimed to see frequency of taste-blindness among the medical students of DG Khan Medical College, Pakistan. Methods: A cross-sectional study was conducted in which simple random sampling technique was applied. Medical students of DG Khan Medical College participated. Out of 381 students, 151 consented (78 female, 73 male) were evaluated for taste blindness. Age range was 17–23 years. A drop of 0.5% PTC solution was placed on the tongue and participants were asked to state the taste perceived. Results: Among males 13.70% and 14.10% females were taste blind to PTC respectively. On regional basis, 13.50% students of upper Punjab and 11.96% students of South Punjab were non-taster to PTC. Conclusion: So, 12.58% population of Punjab is taste blind. Pak J Physiol 2014;10(3-4):10–1